Evaluating the effect of surface treatments and adhesive systems on shear bond strength and microleakage in 3D permanent resin denture bases - Emel Arslan; Hatice Sevmez; Merve Hatice Arslan (BMC Oral Health)
Abstract Objective The objective of this study was to evaluate and compare microleakage and bond strength values resulting from various surface treatments and adhesive system processes applied to different resin materials. Methods 270 samples of two different 3D resin materials (Saremco Crowntec-Saremco Denture) were prepared by various surface treatments (control: Group C, hydrofluoric acid application: Group A, tribochemical sandblasting: Group T), adhesive systems (bond: Group B, resin cement: Group R, resin: Group P) (n = 30). Microleakage and bond strength tests were performed, and the data obtained were analyzed by a two-way ANOVA. Results The findings revealed statistically significant differences among the analyzed groups (p < 0.001). While the mean values of microleakage in Group C were the highest (0.15 ± 0.04 mm2), no significant difference was found between Group A (0.13 ± 0.05 mm2) and Group T (0.14 ± 0.03 mm2). When the bond strength was compared, Group B showed the highest bond strength value (8.50 ± 1.79 MPa) while Group P showed the lowest bond strength value (3.08 ± 1.61 MPa). Significance The study found that applying Group A (2.50 ± 1.47 MPa) weakened the bond, while Group T (3.78 ± 2.63 MPa) had lower values than Group C (13.52 ± 1.37 MPa). Among the adhesive systems, bond application showed the best performance. The application of surface treatment decreases bond strength with reduced microleakage. These findings emphasize the importance of selecting appropriate adhesive systems for 3D-printed complete dentures in clinical applications. It shows the best ways for both clinicans and patients to bond in order to meet the mechanical and aesthetic needs that come up with long-term prostheses use.